تقييم الإطار القانوني لمنصب الأمين العام للبلدية في الجزائر 2011-2017 - بن عياش, سمير (جامعة الوادي University of Eloued, 2018)
العنوان: تقييم الإطار القانوني لمنصب الامين العام للبلدية في الجزائر 2011-2017 إعداد: د/ سمير بن عياش، كلية الحقوق، جامعة أمحمد بوقرة بومرداس .* الملخص: استدعت المرحلة الراهنة إعادة النظر في مكانة الأمين للبلدية بسبب تراكم المشاكل المترتبة عن التسيير المحلي، وتأثير ذلك على تنامي الاحتجاجات المحلية في مختلف الأقاليم، كما تزامن ذلك مع الفشل المتكرر للمجالس البلدية المنتخبة في القيام بواجباتها وانتشار ظاهر الانسداد لهذه المجالس ووقوعها ضحية للصراعات الحزبية بدل خدمة الشأن المحلي، كما تميزت المرحلة بما يعرف بالربيع العربي بالكثير من الأنظمة العربية وانتشار موجة التغيير، فكان لهذا العامل الخارجي التأثير الكبير لضرورة الاستقرار بالجماعات المحلية وزيادة الرقابة الوصائية عليه، وتفادي التهديدات التي ستأثر لا محالة على النظام السياسي، كما تزامنت مع موجة اصلاحات عرفتها الجزائر سمحت بوضع آليات جديدة تسمح للجماعات المحلية من المشاركة بفعالية في وضع برامج التنمية المحلية والعمل على انجاح اصلاحات النظام السياسي بعد 2011 على المستوى المحلي، فهناك حاجة لفواعل تضمن الاستقرار للبلديات بمنحها الصلاحيات اللازمة وبفضل الاهتمام بعملية الاتصال وإعادة الثقة بين المواطنين والسلطة المحلية، لذلك كان الاهتمام أكبر بالأمين العام للبلدية، الشيء الذي يجعل من هذا الأخير أقرب لسلطة عدم التركيز الاداري منه من اللامركزية. Title: The evaluation of the legal framework for general secretary post of the municipality in Algeria 2011-2017 Prepared by: Dr. Samir Ben Ayache, Faculty of Law, University of Boumerdes. Abstract: The current period, required a reconsideration to the secretary's position of the municipality, because of the accumulation of problems arising from local governance. and the impact on the growing local protests in different regions, all This coincided with the repeated failure of the elected municipal councils to carry out their duties, and the spread of the apparent blockage of these councils and their becoming victims of partisan conflicts instead of serving local affairs. This period which known as the Arab spring with the spread changing of regimes in many Arab countries and the spread of the wave of change, was this external factor of the great impact of the need for stability in local communities and increased custodial control . And to avoid threats that will affect the political system; As it coincided with a wave of reforms known by Algeria that allowed the establishment of new mechanisms in order to let the local communities participate effectively in the development of local development programs , and work to ensure the success of reforms of the political system after 2011 at the local level ;There is a need to ensure the stability to the municipalities by giving them the necessary powers, by giving impotence and the process of communication and the restoration of trust between citizens and the local authority. Therefore, the attention was greater to the Secretary-General of the municipality, which makes the latter closer to the authority of the lack of administrative focus than decentralization.
Keywords: التسيير المحلي الجزائر؛الامين العام للبلدية؛ عدم التركيز؛ اللامركزية؛ الرقابة الوصائية. local governance; Algeria; general secretary of the municipality; lack of focus; decentralization; custodial control.